Internet of Things Adoption in the Manufacturing Sector: A Conceptual Model from a Multi-Theoretical Perspective - Ahmetoglu S.; Che Cob Z.; Ali N. (MDPI, 2024)
The manufacturing sector (MS) is considered one of the most important national economic sectors